Information needs of young women vaccinated against HPV attending colposcopy: a qualitative study - Ailie Young; Seonaidh Cotton; Margaret Eleanor Cruickshank (BMC, 2018)
Abstract Background Previous studies have shown that woman attending their first cervical screening or colposcopy appointment experience negative emotions, primarily anxiety and fear. With the introduction of the Human Papillomavirus (HPV) vaccine, it is unknown whether these emotions will have altered or whether the information needs of vaccinated women will have changed. The objective of this study is to determine the knowledge, understanding and concerns that young women have about HPV when attending colposcopy and whether their information needs are met. Methods This is a qualitative study using semi-structured interviews which were audiotaped and transcribed. Data was analysed thematically, with recruitment until data saturation was reached. Women born after 01/09/1990 and attending colposcopy as a result of abnormal cytology were eligible to join the study. Recruitment took place in an out-patient regional colposcopy clinic, Aberdeen, Scotland. Results Fifteen women were interviewed. The majority of participants had some knowledge and understanding of HPV, cervical screening and colposcopy. Knowledge about the HPV vaccine was more limited; a third of participants misunderstood the effectiveness of the vaccine believing that is provided complete protection, and were left feeling that it had failed them. Some also felt that they were "test cases" for the vaccine. Conclusion With the introduction of the HPV vaccine, the information and support needs of young women attending colposcopy are not fully met, leaving women with unanswered questions. With increasing numbers of vaccinated women entering the screening programme, it is timely to review the information available to these women.